Miniscrew-assisted rapid palatal expansion (MARPE): how to achieve greater stability. In vitro study - Flávio de Mendonça COPELLO; Daniel Paludo BRUNETTO; Carlos Nelson ELIAS; Matheus Melo PITHON; Raildo Silva COQUEIRO; Amanda Cunha Regal de CASTRO; Eduardo Franzotti SANT'ANNA (Dental Press Editora, 2021)
ABSTRACT Objective: Assess the influence of mono- and bicortical anchorage and diameter of mini-implants (MIs) on the primary stability of these devices. Methods: 60 self-drilling MIs were distributed in six groups according to diameter (1.5mm, 1.8mm or 2.0mm) and type of anchorage (monocortical and bicortical) in bovine rib. The primary stability was evaluated by insertion torque, micromobility and pull-out strength tests. ANOVA and/or Tukey analysis were used to conduct intergroup comparisons (p< 0.05). Non-parametric statistics (Kruskal-Wallis and Mann-Whitney) were performed when normality was not found (p< 0.05). Results: MIs with larger diameters and bicortical anchorage showed greater primary stability regarding insertion torque (p< 0.05) and micromobility (p< 0.05). Only MI diameter had an effect on the pull-out strength test. Larger diameter MIs presented better retention in pull-out strength tests (p< 0.001), regardless of mono- or bicortical anchorage. Conclusions: MI primary stability is dependent on its diameter and type of anchorage. Bicortical anchorage showed greater stability when compared with monocortical anchorage, independently of other variables.